Non-office-hours admission affects intravenous thrombolysis treatment times and clinical outcome - Zonneveld, Thomas P.; Hametner, Christian; Ringleb, Peter A. (Journal of neurology, neurosurgery, and psychiatry, 2018)
In patients treated with intravenous thrombolysis (IVT), an unfavourable ‘non-office-hours effect’ on door-to-needle time (DNT) and clinical outcome has been suggested. This effect has been attributed to a number of factors, mostly related to either less efficient logistics or less (experienced) staffing during non-office hours (NH). These factors could result in longer DNTs and more protocol violations and thus in worse clinical outcome. On the other hand, one could also argue that the workload during NH is lower, which could result in less time delays in the various diagnostic processes and thus in better clinical outcome. Our hypothesis is that admission during NH has a negative effect on onset-to-needle time (ONT), DNT and clinical outcome in IVT patients. - - The ThRombolysis in Ischaemic Stroke Patients (TRISP) study is a collaboration of 12 European stroke centres and comprises a cohort of over 10 000 consecutive patients treated with IVT.1 We used data of patients treated up to 31 December 2014 (see online supplementary appendix file 1). We excluded patients receiving additional mechanical thrombectomy, those with symptom onset during hospital stay and those who woke up with stroke symptoms. Office hours (OH) and national or regional holidays were collected for each participating centre. Patients were categorised as admitted during NH if their door time was outside OH or during holidays. Outcome and safety measures were ONT, DNT, symptomatic intracerebral haemorrhage (according to European Cooperative Acute Stroke Study II criteria), 3-month mortality and 3-month functional outcome assessed with the modified Rankin Scale . - - ### Supplementary file 1 - - [SP1.pdf] - - Baseline characteristics and treatment times were compared between patients admitted during NH and OH using χ2 tests, Student’s t-tests and Mann-Whitney U tests, where appropriate. In the multivariate ONT and …